Sustainable Management by Forest Farmer Group in Serayu Watershed - Sari, Lilik Kartika; Cahyo, Tri Nur; Kamaluddin, Ridlwan; Setyowati, Endang Ariyani; Khotimah, Alya Husnul (Technium Sustainability, 2025)
The conservation and development management of watersheds require comprehensive studies, planning, and implementation from the upstream water sources to the downstream areas. The active involvement of stakeholders, including government entities responsible for policies, regulations, and budgets, as well as civil society groups such as forest farmer communities, fishermen, business groups, environmental activists, and empowerment advocates, is essential. This research focuses on watershed management among forest farmer groups in the Serayu River area, the longest river in Central Java, specifically in Cilacap and Banyumas Regencies of Indonesia A qualitative explanatory case study method was employed, utilizing direct observation, in-depth interviews, document analysis, and discussions. Data were analyzed through reduction, classification, clarification, and triangulation. The findings reveal that the management of the Serayu River watershed still requires socialization, coordination, and collaboration among stakeholders in planning, conservation, maintenance, development, monitoring, and evaluation. These stakeholders include local and village governments, socio-economic community groups, private entities, and academics. Relevant watershed management approaches include conceptual, deterministic, stochastic, parametric, and probabilistic methods.